A framework for implementing mobile interactive lecture information systems in Higher Learning Institutions / Gan Chin Lay - Gan, Chin Lay (2016)

(untitled)
The basis for conducting this research is the potential of mobile technology to aid and increase interactions between students and lecturers in higher education. The determination of key predictors of mobile technology adoption, and its effects on studentlecturer interactions, defined the overall direction of this research. The Interactive Mobile Messaging Acceptance framework was established with system quality, information quality, perceived usefulness, perceived ease of use, enjoyment, self-efficacy, and uncertainty avoidance as the independent variables (predictors), and adoption intention of mobile technology to aid student-lecturer interactions as the dependent variable. Therefore, this research attempts to investigate the impact of the predictors on the adoption intention of mobile technology. A mix method approach was undertaken in this research. Findings from observations of large lecture classes confirmed the negative effects of large classes on student-lecturer interactions. Semi-structured interviews with academics of higher education using nonprobability quota sampling method was conducted. Thematic analysis was applied to the qualitative data collected from the interviews. Overall, lack of interactions was perceived as the norm of large classes. Perceptions on the potential of mobile technology to aid interactions with their students were favourable, however, reservations relating to the suitability of using mobile technology in the classrooms were also expressed. The research then commenced to the quantitative phase. A non-probability convenience sampling was used to collect data from tertiary students in Malaysia. Exploratory factor analysis was applied, and the underlying structure of the framework was confirmed. Partial least squares path modelling was applied to assess the reliability and validity of the framework, and to test the hypotheses. Lastly, importance-performance matrix analysis was applied to extend the findings. Findings supported the significance iv of system quality, information quality, enjoyment, and uncertainty avoidance construct, pointing to the relevance of mobile technology’s features, and feelings of satisfaction or pleasure when using the technology. Lower uncertainty level has a small effect on adoption intention of mobile technology. Findings failed to support the significance of perceived ease of use, perceived usefulness, and self-efficacy. Next, the Interactive Mobile Messaging Application (IMMAP) was developed using the framework as a guide. A pretest-posttest experimental procedure was undertaken to assess IMMAP’s feasibility to aid student-lecturer interactions. Significant differences were detected for the enjoyment (lower), uncertainty avoidance (lower) and system quality (higher) of IMMAP, as well as overall intentions to use IMMAP in future classes (higher). Therefore, functional features that can increase user enjoyment when using IMMAP must be given careful considerations in future enhancements. This research makes several theoretical and practical contributions, and provides further insights on mobile technology acceptance in higher education to support studentlecturer interactions. Theoretical, methodological, and educational implications were discussed, and several suggestions for future research were identified and recommended. In short, this research helped to further the understanding on the educational use of mobile technology in higher education.